A proxy for privacy uncovering the surveillance ecology of mobile apps. Issue 2 (July 2020) - Sophus Lai, Signe; Flensburg, Sofie
The article develops a methodological and empirical approach for gauging the ways Big Data can be collected and distributed through mobile apps. This approach focuses on the infrastructural components that condition the disclosure of smartphone users' data – namely the permissions that apps request and the third-party corporations they work with. We explore the surveillance ecology of mobile apps and thereby the privacy implications of everyday smartphone use through three analytical perspectives: The first focuses on the 'appscapes' of individual smartphone users and investigates the consequences of which and how many mobile apps users download on their phones; the second compares different types of apps in order to study the app ecology and the relationships between app and third-party service providers; and the third focuses on a particular app category and discusses the functional as well as the commercial incentives for permissions and third-party collaborations. Thereby, the article advances an interdisciplinary dialogue between critical data studies, political economy and app studies, and pushes an empirical and critical perspective on mobile communication, app ecologies and data economies.